High-strength environment-friendly ceramsite crack proppant
By developing a high-strength environmentally friendly ceramic crack proppant, using a variety of surface-modified materials and bio-based polymers to form a composite network structure, the environmental and cost problems of traditional proppants are solved, and efficient and environmentally friendly petroleum mining proppant is achieved.
Patent Information
- Application Number
- CN202411693849.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Traditional oil mining proppants have environmental pollution problems during production, use and waste, and are expensive and difficult to achieve large-scale application.
A high-strength environmentally friendly ceramic crack proppant was developed to form a multi-layered and fully functional composite network structure through the combination of surface silanized modified fly ash, surface activated quartz sand, surface modified basalt fibers, surface carboxylated graphene nanosheets, surface carboxylated carbon nanotubes, bio-based polyurethane, polyaluminum phosphate corrosion resistance and polyethylene glycol lubricant.
This proppant not only significantly improves mechanical strength, corrosion resistance and electrical conductivity, but also achieves efficient utilization of resources and sustainable environmental protection by utilizing industrial waste and renewable resources, meeting the multiple needs of modern industry for efficient and environmentally friendly materials.
Smart Images

Figure BDA0005151648170000131 
Figure BDA0005151648170000141 
Figure BDA0005151648170000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil extraction, and in particular to a high-strength environmentally friendly ceramsite fracture proppant and a preparation method thereof. Background Art
[0002] In the modern oil production process, proppants, as key materials in hydraulic fracturing technology, play an important role in maintaining and supporting fracturing cracks and ensuring the smooth flow of oil and gas. Traditional proppants mainly use silica sand, ceramic particles and synthetic polymer materials. These materials are widely used in oil and gas production operations under various geological conditions due to their excellent mechanical strength and stability. However, with the enhancement of global environmental protection awareness and the popularization of the concept of sustainable development, the environmental problems caused by traditional proppants in the production, use and disposal process have become increasingly prominent. The mining of silica sand not only consumes a lot of water resources and energy, but also causes damage to the ecosystem, such as land degradation and destruction of biological habitats. In addition, the transportation process of silica sand involves high energy consumption and a large amount of carbon emissions, which further aggravates the environmental burden. Although ceramic proppants have improved mechanical properties, their production process is complicated and costly, making it difficult to achieve large-scale application. At the same time, synthetic polymer materials have shortcomings in environmental friendliness and are difficult to meet increasingly stringent environmental protection requirements.
[0003] In this context, the development of high-strength and environmentally friendly ceramsite fracture proppants has become a technical problem that needs to be solved urgently in the field of materials science. Environmentally friendly proppants not only need to be comparable to traditional proppants in mechanical properties, but even surpass them in some aspects to adapt to the harsh requirements of high-pressure, high-temperature and complex geological conditions, but also need to be environmentally friendly in material selection and preparation process. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present invention provides a high-strength environmentally friendly ceramsite fracture proppant, which comprises the following components by weight:
[0005] 57-63 parts of fly ash with surface silanization modification;
[0006] 28-32 parts of surface activated quartz sand;
[0007] 4-6 parts of surface-modified basalt fibers;
[0008] 2-4 parts of surface carboxylated graphene nanosheets;
[0009] 1.5-2.5 parts of surface carboxylated carbon nanotubes;
[0010] 1.5-2.5 parts of bio-based polyurethane with NCO and OH functional groups;
[0011] 0.8-1.2 parts of aluminum polyphosphate corrosion inhibitor;
[0012] 0.8-1.2 parts of polyethylene glycol lubricant.
[0013] Furthermore, the preparation method of the surface silanized fly ash comprises:
[0014] The particle size is 20-45μm and the specific surface area is 350-450m 2 / g of fly ash is vacuum dried at 80-100°C for 4-6 hours;
[0015] Disperse the dried fly ash in anhydrous ethanol, add 3-5wt% of silane coupling agent KH550, and stir and react at 60-70°C for 2-3 hours;
[0016] Filter, wash and dry at 60-80°C for 8-12 hours to obtain fly ash with surface silanization modification.
[0017] Furthermore, the preparation method of the surface activated quartz sand comprises:
[0018] Quartz sand with a particle size of 45-75 μm and a purity of ≥99.5% was ultrasonically cleaned with deionized water and anhydrous ethanol in sequence;
[0019] Soak the cleaned quartz sand in a 10-15wt% NaOH solution at 90-95°C for 1-2 hours;
[0020] Neutralize with dilute HCl to neutrality, wash with water and dry to obtain surface-activated quartz sand.
[0021] Furthermore, the preparation method of the surface-modified basalt fiber includes:
[0022] The basalt fiber with an aspect ratio of 100-150 is vacuum dried at 120-150°C for 2-3 hours;
[0023] The dried fiber is immersed in a 3-5wt% silane coupling agent KH560 solution and ultrasonically treated at room temperature for 30-60 minutes;
[0024] The product is filtered, washed, and dried at 80-100° C. for 4-6 hours to obtain surface-modified basalt fibers.
[0025] Furthermore, the method for preparing the surface carboxylated graphene nanosheets comprises:
[0026] The specific surface area ≥800m 2 / g of graphene nanosheets were dispersed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1);
[0027] Ultrasonic treatment at 60-70°C for 2-3 hours;
[0028] The mixture was filtered and washed with water until neutral, and vacuum dried at 60-80° C. for 12 hours to obtain graphene nanosheets with surface carboxylation.
[0029] Furthermore, the method for preparing the surface carboxylated carbon nanotubes comprises:
[0030] The specific surface area ≥ 600m 2 / g of carbon nanotubes were dispersed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1);
[0031] Ultrasonic treatment at 70-80°C for 3-4 hours;
[0032] The product was filtered and washed with water until neutral, and dried under vacuum at 80-100° C. for 12 hours to obtain carbon nanotubes with surface carboxylation.
[0033] Furthermore, the method for preparing the bio-based polyurethane having NCO and OH functional groups comprises:
[0034] Castor oil and polyethylene glycol are used as raw materials and mixed in a molar ratio of 1:1;
[0035] Add diisocyanate and stir the reaction at 60-70°C for 2-3 hours;
[0036] After cooling to room temperature, a bio-based polyurethane with NCO and OH functional groups was obtained.
[0037] Furthermore, the particle size of the polyaluminum phosphate corrosion inhibitor is 0.5-1 μm.
[0038] Furthermore, the molecular weight of the polyethylene glycol lubricant is 2000-4000.
[0039] Furthermore, the preparation method of the composite proppant includes:
[0040] Mix the components in proportion and add 30-40% by volume of anhydrous ethanol;
[0041] Mix well in a high-speed mixer at a speed of 800-1000 rpm for 15-20 minutes;
[0042] The composite proppant is obtained by drying at 80-100° C. for 4-6 hours.
[0043] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present invention.
[0044] Beneficial technical effects of the present invention:
[0045] The high-strength and environmentally friendly ceramsite fracture proppant of the present invention forms a multi-level and fully functional composite network structure through chemical reactions and physical complementarity between the components. This structure not only significantly improves the mechanical strength, corrosion resistance and electrical conductivity of the material, but also realizes efficient resource utilization and sustainable environmental protection by utilizing industrial waste and renewable resources. The synergistic effect of the components at the molecular level enables the composite proppant to find a perfect balance between high performance and green environmental protection, meeting the multiple demands of modern industry for efficient and environmentally friendly materials, and showing broad application prospects and significant market competitiveness. DETAILED DESCRIPTION
[0046] The optional embodiments of the present invention will be described in more detail below. Although the optional embodiments of the present invention are described, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0047] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0048] The present invention provides a high-strength environmentally friendly ceramsite fracture proppant, which comprises the following components by weight:
[0049] 57-63 parts of fly ash with surface silanization modification;
[0050] 28-32 parts of surface activated quartz sand;
[0051] 4-6 parts of surface-modified basalt fibers;
[0052] 2-4 parts of surface carboxylated graphene nanosheets;
[0053] 1.5-2.5 parts of surface carboxylated carbon nanotubes;
[0054] 1.5-2.5 parts of bio-based polyurethane with NCO and OH functional groups;
[0055] 0.8-1.2 parts of aluminum polyphosphate corrosion inhibitor;
[0056] 0.8-1.2 parts of polyethylene glycol lubricant.
[0057] In one embodiment of the present invention, the preparation method of the surface silanized fly ash comprises:
[0058] The particle size is 20-45μm and the specific surface area is 350-450m 2 / g of fly ash is vacuum dried at 80-100°C for 4-6 hours;
[0059] Disperse the dried fly ash in anhydrous ethanol, add 3-5wt% of silane coupling agent KH550, and stir and react at 60-70°C for 2-3 hours;
[0060] Filter, wash and dry at 60-80°C for 8-12 hours to obtain fly ash with surface silanization modification.
[0061] In one embodiment of the present invention, the method for preparing the surface activated quartz sand comprises:
[0062] Quartz sand with a particle size of 45-75 μm and a purity of ≥99.5% was ultrasonically cleaned with deionized water and anhydrous ethanol in sequence;
[0063] Soak the cleaned quartz sand in a 10-15wt% NaOH solution at 90-95°C for 1-2 hours;
[0064] Neutralize with dilute HCl to neutrality, wash with water and dry to obtain surface-activated quartz sand.
[0065] In one embodiment of the present invention, the preparation method of the surface-modified basalt fiber comprises:
[0066] The basalt fiber with an aspect ratio of 100-150 is vacuum dried at 120-150°C for 2-3 hours;
[0067] The dried fiber is immersed in a 3-5wt% silane coupling agent KH560 solution and ultrasonically treated at room temperature for 30-60 minutes;
[0068] The product is filtered, washed, and dried at 80-100° C. for 4-6 hours to obtain surface-modified basalt fibers.
[0069] First, the surface silanized fly ash (57-63 parts) forms silicon-oxygen bonds on its surface through a silane coupling agent (such as KH550), which not only enhances the interfacial adhesion between fly ash and other inorganic components (such as quartz sand and basalt fiber), but also effectively utilizes industrial waste and reduces environmental burden. After the surface activated quartz sand (28-32 parts) is treated with NaOH, its surface hydroxyl content increases, improving the chemical compatibility with fly ash and polyurethane matrix, forming a more stable silicon-oxygen network structure, and significantly improving the mechanical strength and stability of the composite material.
[0070] Surface-modified basalt fibers (4-6 parts) form covalent bonds with NCO and OH functional groups in bio-based polyurethane (1.5-2.5 parts) through silane coupling agents (such as KH560). This chemical bond not only enhances the interfacial bonding between the fiber and the matrix, but also improves the tensile and bending properties of the material by dispersing stress. Nanoscale surface carboxylated graphene nanosheets (2-4 parts) and carbon nanotubes (1.5-2.5 parts) are treated with carboxylation to form more carboxyl groups that react with functional groups in polyurethane, promoting the uniform dispersion of nanofillers in the matrix and significantly improving the mechanical strength, conductivity and thermal stability of the composite material. In addition, polyaluminum phosphate anticorrosive agent (0.8-1.2 parts) effectively inhibits corrosion reactions and prolongs the service life of the material by forming complexes with metal ions in the composite material. At the same time, its nanoscale particle size ensures the uniform distribution of the anti-corrosion effect.
[0071] Polyethylene glycol lubricant (0.8-1.2 parts) improves the fluidity and processing performance of the composite material through interaction with other components, ensuring that the components can be evenly distributed during high-temperature drying to prevent stress concentration and cracks inside the material. In addition, as a renewable resource, the NCO and OH functional groups in the molecular structure of bio-based polyurethane not only provide multi-point cross-linking sites and enhance the stability of the overall network structure, but also reduce dependence on petroleum-based materials and reduce carbon footprint through the use of renewable materials.
[0072] In one embodiment of the present invention, the method for preparing the surface carboxylated graphene nanosheets comprises:
[0073] The specific surface area ≥800m 2 / g of graphene nanosheets were dispersed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1);
[0074] Ultrasonic treatment at 60-70°C for 2-3 hours;
[0075] The mixture was filtered and washed with water until neutral, and vacuum dried at 60-80° C. for 12 hours to obtain graphene nanosheets with surface carboxylation.
[0076] In one embodiment of the present invention, the method for preparing the surface carboxylated carbon nanotubes comprises:
[0077] The specific surface area ≥ 600m 2 / g of carbon nanotubes were dispersed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1);
[0078] Ultrasonic treatment at 70-80°C for 3-4 hours;
[0079] The product was filtered and washed with water until neutral, and dried under vacuum at 80-100° C. for 12 hours to obtain carbon nanotubes with surface carboxylation.
[0080] In one embodiment of the present application, the method for preparing the bio-based polyurethane having NCO and OH functional groups comprises:
[0081] Castor oil and polyethylene glycol are used as raw materials and mixed in a molar ratio of 1:1;
[0082] Add diisocyanate and stir the reaction at 60-70°C for 2-3 hours;
[0083] After cooling to room temperature, a bio-based polyurethane with NCO and OH functional groups was obtained.
[0084] In one embodiment of the present invention, the particle size of the polyaluminum phosphate corrosion inhibitor is 0.5-1 μm.
[0085] In one embodiment of the present application, the molecular weight of the polyethylene glycol lubricant is 2000-4000.
[0086] In one embodiment of the present invention, the preparation method of the composite proppant comprises:
[0087] Mix the components in proportion and add 30-40% by volume of anhydrous ethanol;
[0088] Mix well in a high-speed mixer at a speed of 800-1000 rpm for 15-20 minutes;
[0089] The composite proppant is obtained by drying at 80-100° C. for 4-6 hours.
[0090] For the purpose of greater clarity, the invention is described in detail through the following examples.
[0091] Embodiment 1:
[0092] Formula composition (by weight):
[0093] Surface silanized fly ash: 57 parts
[0094] Surface activated quartz sand: 28 parts
[0095] Surface modified basalt fiber: 4 parts
[0096] Surface carboxylated graphene nanosheets: 2 parts
[0097] Surface carboxylated carbon nanotubes: 1.5 parts
[0098] Bio-based polyurethane with NCO and OH functional groups: 1.5 parts
[0099] Aluminum polyphosphate corrosion inhibitor: 0.8 parts
[0100] Polyethylene glycol lubricant: 0.8 parts
[0101] Preparation steps:
[0102] Fly ash treatment: Particle size 20μm, specific surface area 350m 2 / g of fly ash is vacuum dried at 80°C for 4 hours; the dried fly ash is dispersed in anhydrous ethanol, 3wt% of KH550 silane coupling agent is added, and the mixture is stirred and reacted at 60°C for 2 hours; after filtration and washing, the mixture is dried at 60°C for 8 hours to obtain surface silanized fly ash.
[0103] Quartz sand treatment: Quartz sand with a particle size of 45 μm and a purity of 99.5% was ultrasonically cleaned with deionized water and anhydrous ethanol in turn; immersed in a 10 wt % NaOH solution and treated at 90° C. for 1 hour; neutralized to neutrality with dilute HCl, washed with water, and dried to obtain surface-activated quartz sand.
[0104] Basalt fiber treatment: basalt fiber with an aspect ratio of 100 was vacuum dried at 120° C. for 2 hours; immersed in a 3wt% KH560 silane coupling agent solution and ultrasonically treated at room temperature for 30 minutes; filtered, washed, and dried at 80° C. for 4 hours to obtain surface-modified basalt fiber.
[0105] Graphene nanosheet processing: Surface area of 800m 2 / g of graphene nanosheets were dispersed in concentrated sulfuric acid and concentrated nitric acid (volume ratio of 3:1), and ultrasonically treated at 60°C for 2 hours; filtered, washed with water until neutral, and vacuum dried at 60°C for 12 hours to obtain surface carboxyl-grouped graphene nanosheets.
[0106] Carbon nanotube processing: Surface area 600m 2 / g of carbon nanotubes were dispersed in concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1), and ultrasonically treated at 70°C for 3 hours; filtered, washed with water until neutral, and vacuum dried at 80°C for 12 hours to obtain surface carboxyl carbon nanotubes.
[0107] Preparation of bio-based polyurethane: Castor oil and polyethylene glycol were mixed in a molar ratio of 1:1, diisocyanate was added, and the mixture was stirred and reacted at 60° C. for 2 hours; the mixture was cooled to room temperature to obtain a bio-based polyurethane having NCO and OH functional groups.
[0108] Preparation of composite proppant: Mix the components according to the above weight proportions, add 30% anhydrous ethanol; stir at 800 rpm in a high-speed stirrer for 15 minutes to mix evenly; dry at 80° C. for 4 hours to obtain a high-strength environmentally friendly ceramsite fracture proppant.
[0109] Embodiment 2:
[0110] Formula composition (by weight):
[0111] Surface silanized fly ash: 60 parts
[0112] Surface activated quartz sand: 30 parts
[0113] Surface modified basalt fiber: 5 parts
[0114] Surface carboxylated graphene nanosheets: 3 parts
[0115] Surface carboxylated carbon nanotubes: 2 parts
[0116] Bio-based polyurethane with NCO and OH functional groups: 2 parts
[0117] Aluminum polyphosphate corrosion inhibitor: 1 part
[0118] Polyethylene glycol lubricant: 1 part
[0119] Preparation steps:
[0120] Fly ash treatment: Particle size 30μm, specific surface area 400m 2 / g of fly ash is vacuum dried at 90°C for 5 hours; the dried fly ash is dispersed in anhydrous ethanol, 4wt% of KH550 silane coupling agent is added, and the mixture is stirred and reacted at 65°C for 2.5 hours; after filtration and washing, the mixture is dried at 70°C for 10 hours to obtain surface silanized fly ash.
[0121] Quartz sand treatment: Quartz sand with a particle size of 60 μm and a purity of 99.5% was ultrasonically cleaned with deionized water and anhydrous ethanol in turn; immersed in a 12.5wt% NaOH solution and treated at 92.5°C for 1.5 hours; neutralized to neutrality with dilute HCl, washed with water, and dried to obtain surface-activated quartz sand.
[0122] Basalt fiber treatment: basalt fiber with an aspect ratio of 125 was vacuum dried at 135° C. for 2.5 hours; immersed in a 4wt% KH560 silane coupling agent solution and ultrasonically treated at room temperature for 45 minutes; filtered, washed, and dried at 90° C. for 5 hours to obtain surface-modified basalt fiber.
[0123] Graphene nanosheet processing: Surface area of 900m 2 / g of graphene nanosheets were dispersed in concentrated sulfuric acid and concentrated nitric acid (volume ratio of 3:1), and ultrasonically treated at 65°C for 2.5 hours; filtered and washed with water until neutral, and vacuum dried at 70°C for 12 hours to obtain surface carboxylated graphene nanosheets.
[0124] Carbon nanotube processing: Surface area 700m 2 / g of carbon nanotubes were dispersed in concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1), and ultrasonically treated at 75°C for 3.5 hours; filtered, washed with water until neutral, and vacuum dried at 90°C for 12 hours to obtain surface carboxyl carbon nanotubes.
[0125] Preparation of bio-based polyurethane: Castor oil and polyethylene glycol were mixed in a molar ratio of 1:1, diisocyanate was added, and the mixture was stirred and reacted at 65° C. for 2.5 hours; the mixture was cooled to room temperature to obtain a bio-based polyurethane having NCO and OH functional groups.
[0126] Preparation of composite proppant: Mix the components according to the above weight proportions, add 35% anhydrous ethanol; stir at 900 rpm for 17 minutes in a high-speed stirrer to mix evenly; dry at 90° C. for 5 hours to obtain a high-strength environmentally friendly ceramsite fracture proppant.
[0127] Embodiment 3:
[0128] Formula composition (by weight):
[0129] Surface silanized fly ash: 63 parts
[0130] Surface activated quartz sand: 32 parts
[0131] Surface modified basalt fiber: 6 parts
[0132] Surface carboxylated graphene nanosheets: 4 parts
[0133] Surface carboxylated carbon nanotubes: 2.5 parts
[0134] Bio-based polyurethane with NCO and OH functional groups: 2.5 parts
[0135] Aluminum polyphosphate corrosion inhibitor: 1.2 parts
[0136] Polyethylene glycol lubricant: 1.2 parts
[0137] Preparation steps:
[0138] Fly ash treatment: Particle size 45μm, specific surface area 450m 2 / g of fly ash is vacuum dried at 100°C for 6 hours; the dried fly ash is dispersed in anhydrous ethanol, 5wt% of KH550 silane coupling agent is added, and the mixture is stirred and reacted at 70°C for 3 hours; after filtration and washing, the mixture is dried at 80°C for 12 hours to obtain surface silanized fly ash.
[0139] Quartz sand treatment: Quartz sand with a particle size of 75 μm and a purity of 99.5% was ultrasonically cleaned with deionized water and anhydrous ethanol in turn; immersed in a 15 wt % NaOH solution and treated at 95° C. for 2 hours; neutralized to neutrality with dilute HCl, washed with water, and dried to obtain surface-activated quartz sand.
[0140] Basalt fiber treatment: basalt fiber with an aspect ratio of 150 was vacuum dried at 150°C for 3 hours; immersed in a 5wt% KH560 silane coupling agent solution and ultrasonically treated at room temperature for 60 minutes; filtered, washed, and dried at 100°C for 6 hours to obtain surface-modified basalt fiber.
[0141] Graphene nanosheet processing: Surface area 1000m 2 / g of graphene nanosheets were dispersed in concentrated sulfuric acid and concentrated nitric acid (volume ratio of 3:1), and ultrasonically treated at 70°C for 3 hours; filtered and washed with water until neutral, and vacuum dried at 80°C for 12 hours to obtain surface carboxyl-grouped graphene nanosheets.
[0142] Carbon nanotube processing: Surface area 800m 2 / g of carbon nanotubes were dispersed in concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1), and ultrasonically treated at 80°C for 4 hours; filtered, washed with water until neutral, and vacuum dried at 100°C for 12 hours to obtain surface carboxyl carbon nanotubes.
[0143] Preparation of bio-based polyurethane: Castor oil and polyethylene glycol were mixed in a molar ratio of 1:1, diisocyanate was added, and the mixture was stirred and reacted at 70° C. for 3 hours; the mixture was cooled to room temperature to obtain a bio-based polyurethane having NCO and OH functional groups.
[0144] Preparation of composite proppant: Mix the components according to the above weight proportions, add 40% anhydrous ethanol; stir at 1000 rpm for 20 minutes in a high-speed stirrer to mix evenly; dry at 100° C. for 6 hours to obtain a high-strength environmentally friendly ceramsite fracture proppant.
[0145] Test Example 1
[0146] Objective: To evaluate the physical stability of high-strength and environmentally friendly ceramsite fracture proppant in higher temperature and high pressure reservoir environment and ensure its reliability and effectiveness in various practical applications.
[0147] Method: High temperature and high pressure reactor was used to carry out high temperature and high pressure immersion test in different reservoir environments.
[0148] step:
[0149] Sample preparation:
[0150] The high-strength environmentally friendly ceramsite fracture proppant (Example 2) and traditional silica sand were sieved according to the standard particle size range (20-40 mesh).
[0151] Prepare a certain number of particle samples (e.g. 100 particles).
[0152] Equipment Calibration:
[0153] Calibrate high temperature and high pressure reactors to ensure accurate temperature and pressure control.
[0154] Testing process:
[0155] The proppant particles are placed in a reactor, and fracturing fluid (such as an aqueous solution containing an appropriate amount of salt and a pH regulator) is added.
[0156] To set up multiple test conditions:
[0157] Test group 1: 200°C, 1000ps i, 72 hours
[0158] Test Group 2: 250°C, 1500ps i, 72 hours
[0159] Test Group 3: 300°C, 2000psi, 72 hours
[0160] Test each group of conditions separately.
[0161] After the test, the particles were taken out, cleaned and dried, and the morphological changes and mass loss of the particles were recorded.
[0162] Data Analysis:
[0163] The mass loss percentage (MLP) and particle breakage rate were calculated to evaluate its stability under different high temperature and high pressure environments.
[0164] Experimental data:
[0165]
[0166]
[0167]
[0168] Result analysis:
[0169] Composite proppant:
[0170] 200℃ / 1000psi: The average mass loss rate is 0.2%, and the particle breakage rate is 1.5%, showing extremely high stability.
[0171] 250℃ / 1500psi: The mass loss rate was 0.8% on average, and the particle breakage rate was 1.85%, which increased slightly but still maintained good stability.
[0172] 300℃ / 2000psi: The average mass loss rate is 1.8%, and the particle breakage rate is 2.75%. It still has strong stability under high temperature and high pressure conditions.
[0173] Traditional silica sand:
[0174] Under each test condition, the mass loss rate and particle breakage rate were significantly higher than those of the composite proppant, especially at 300°C / 2000 psi, the breakage rate reached 28%.
[0175] in conclusion:
[0176] By increasing the test temperature to 200°C, 250°C and 300°C, the experimental results further verified the excellent performance of the high-strength environmentally friendly ceramsite fracture proppant of the present invention under higher temperature and high pressure environment:
[0177] High temperature and high pressure stability: The composite proppant can still maintain low mass loss rate and particle breakage rate under conditions of up to 300°C and 2000 psi, which is significantly better than traditional silica sand.
[0178] Strong adaptability: Composite proppants are suitable for a wider range of reservoir environments, especially high-temperature and high-pressure oil wells, ensuring their reliability and effectiveness under various extreme conditions.
[0179] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made based on the present invention. Therefore, these modifications and improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A high-strength environmentally friendly ceramsite fracture proppant, characterized in that: The following components are included by weight: 57-63 parts of fly ash with surface silanization modification; 28-32 parts of surface activated quartz sand; 4-6 parts of surface-modified basalt fibers; 2-4 parts of surface carboxylated graphene nanosheets; 1.5-2.5 parts of surface carboxylated carbon nanotubes; 1.5-2.5 parts of bio-based polyurethane with NCO and OH functional groups; 0.8-1.2 parts of aluminum polyphosphate corrosion inhibitor; 0.8-1.2 parts of polyethylene glycol lubricant.
2. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The preparation method of the fly ash with surface silanization modification comprises: The particle size is 20-45μm and the specific surface area is 350-450m 2 / g of fly ash is vacuum dried at 80-100°C for 4-6 hours; Disperse the dried fly ash in anhydrous ethanol, add 3-5wt% of silane coupling agent KH550, and stir and react at 60-70°C for 2-3 hours; Filter, wash and dry at 60-80°C for 8-12 hours to obtain fly ash with surface silanization modification.
3. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The preparation method of the surface activated quartz sand comprises: Quartz sand with a particle size of 45-75 μm and a purity of ≥99.5% was ultrasonically cleaned with deionized water and anhydrous ethanol in sequence; Soak the cleaned quartz sand in a 10-15wt% NaOH solution at 90-95°C for 1-2 hours; Neutralize with dilute HCl to neutrality, wash with water and dry to obtain surface-activated quartz sand.
4. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The preparation method of the surface-modified basalt fiber comprises: The basalt fiber with an aspect ratio of 100-150 is vacuum dried at 120-150°C for 2-3 hours; The dried fiber is immersed in a 3-5wt% silane coupling agent KH560 solution and ultrasonically treated at room temperature for 30-60 minutes; The product is filtered, washed, and dried at 80-100° C. for 4-6 hours to obtain surface-modified basalt fibers.
5. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The preparation method of the surface carboxylated graphene nanosheets comprises: The specific surface area ≥800m 2 / g of graphene nanosheets were dispersed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1); Ultrasonic treatment at 60-70°C for 2-3 hours; The mixture was filtered and washed with water until neutral, and vacuum dried at 60-80° C. for 12 hours to obtain graphene nanosheets with surface carboxylation.
6. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The method for preparing the surface carboxylated carbon nanotubes comprises: The specific surface area ≥ 600m 2 / g of carbon nanotubes were dispersed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1); Ultrasonic treatment at 70-80°C for 3-4 hours; The mixture was filtered and washed with water until neutral, and vacuum dried at 80-100° C. for 12 hours to obtain carbon nanotubes with surface carboxylation.
7. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The method for preparing the bio-based polyurethane having NCO and OH functional groups comprises: Castor oil and polyethylene glycol are used as raw materials and mixed in a molar ratio of 1:1; Add diisocyanate and stir the reaction at 60-70°C for 2-3 hours; After cooling to room temperature, a bio-based polyurethane with NCO and OH functional groups was obtained.
8. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The particle size of the polyaluminum phosphate anticorrosion agent is 0.5-1 μm.
9. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The molecular weight of the polyethylene glycol lubricant is 2000-4000.
10. The high-strength environmentally friendly ceramsite fracture proppant according to claim 1, characterized in that: The preparation method of the composite proppant comprises: Mix the components in proportion and add 30-40% by volume of anhydrous ethanol; Mix well in a high-speed mixer at a speed of 800-1000 rpm for 15-20 minutes; The composite proppant is obtained by drying at 80-100° C. for 4-6 hours.
Citation Information
Patent Citations
Corrosion-resistant propping agent
CN101768432A
Proppant and preparation method thereof
CN109575907A
Sinking expansion polyurethane with strong tearing property and preparation method thereof
CN112250820A
Ultralow-density synthetic ceramsite proppant and preparation method thereof
CN112441771A
Inorganic fiber reinforced thermoplastic polyurethane composite material and preparation method thereof
CN114855300A
Cited By
Microcrack ceramsite proppant and preparation method thereof
CN120518404A